(untitled) (Sahel Journal of Life Sciences FUDMA, 2026)
The soil fertility status of the Pella District was assessed to determine some physical and chemical properties, where soil samples were taken from 11 units and subjected to standard laboratory procedures. Results showed that the soils were mostly sandy loam. Soil pH was slightly acidic to neutral, and electrical conductivity (EC), organic carbon, available phosphorus and calcium consistently showed both low to medium values. Sodium (Na) showed medium to high values, Potassium (K) and molybdenum (Mo) had low, medium and high values. Total exchangeable bases (TEB) and Sulphur (S) showed medium values, while total exchangeable acidity (TEA) and Effective cation exchange capacity (ECEC) were low. Nutrient Fertility index (NFI) of P, S and Mo indicates medium as per phosphorus (P) and molybdenum (Mo) with values of (1.9) and (1.9) respectively, while Sulphur (S) showed a low value of (1.0). The soil’s fertility status of the study area was generally low with S as one of the limiting nutrients; therefore, site- specific soil management, including Sulphur fertilization, is recommended. Over-application of nitrogen, especially nitrate-based fertilizer, should be avoided.